2009
DOI: 10.1088/1741-2560/6/5/056005
|View full text |Cite
|
Sign up to set email alerts
|

The design and hardware implementation of a low-power real-time seizure detection algorithm

Abstract: Epilepsy affects more than 1% of the world's population. Responsive neurostimulation is emerging as an alternative therapy for the 30% of the epileptic patient population that does not benefit from pharmacological treatment. Efficient seizure detection algorithms will enable closed-loop epilepsy prostheses by stimulating the epileptogenic focus within an early onset window. Critically, this is expected to reduce neuronal desensitization over time and lead to longer-term device efficacy. This work presents a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…However, all of them lack the ability to process real-time data. While some reports have described realtime SWD detection (Raghunathan et al, 2009;Talathi et al, 2008), the proposed techniques have all shown relatively low performance. Here we propose and evaluate a CWT method for real-time detection of SWDs in ECoG using rats of the WAG/Rij strain (van Luijtelaar and Coenen, 1986;van Luijtelaar and Sitnikova, 2006), and compare its performance against visual scoring.…”
Section: Introductionmentioning
confidence: 94%
“…However, all of them lack the ability to process real-time data. While some reports have described realtime SWD detection (Raghunathan et al, 2009;Talathi et al, 2008), the proposed techniques have all shown relatively low performance. Here we propose and evaluate a CWT method for real-time detection of SWDs in ECoG using rats of the WAG/Rij strain (van Luijtelaar and Coenen, 1986;van Luijtelaar and Sitnikova, 2006), and compare its performance against visual scoring.…”
Section: Introductionmentioning
confidence: 94%
“…The marked out seizures included both clinical and sub-clinical events based on electrographic inspection. We have previously documented these methods in (Raghunathan et al, 2009a). The seizures were classified from 1 to 5 on a Racine scale, per published protocols (Hellier and Dudek, 2005).…”
Section: Seizure Identification and Analysismentioning
confidence: 99%
“…The Neuropace ® device provides a platform for incorporating highly efficient, hardware-optimized detection algorithms that can be implemented using microchips that can operate with orders of magnitude lower power consumption than standard microcontrollers (Raghunathan et al, 2009a). The analysis performed in this paper compares a set of published seizure detection features and evaluates them from a dual viewpoint of both detection and hardware efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, recent studies [5][6][7][8] ing low power on real-time implantable devices. However, these low power, computationally-efficient (i.e., lightweight) seizure detection algorithms use only timedomain features including indirect frequency features such as count-based, and inter-event due to the computational complexity of frequency-domain feature computation.…”
Section: Introductionmentioning
confidence: 99%